Effect of Plasmonic Au and Ag/Au Nanoparticles and Sodium Citrate on the Optical Properties of Chitin-Based Photonic Nanoarchitectures in Butterfly Wing Scales - Krisztián Kertész; Gábor Piszter; Zsolt Endre Horváth; Dániel Zámbó; András Deák; László Péter Biró (Photonics, 2022)
Porous butterfly wings with hierarchically organized structures from nanometer to centimeter scales were tested as substrates for carrying plasmonic Au and Ag/Au nanoparticles with potential application in photocatalysis. Wings exhibiting structural color generated by chitin-air nanocomposites were used. Hundreds of butterfly species possess these types of color-generating photonic nanoarchitectures, producing color by a similar mechanism to manmade photonic crystals. Artificial photonic crystals are known to enhance photocatalytic processes through the slow light effect. The impact of pure water, water-based sodium citrate solution, and Au and Ag/Au alloy nanoparticles on the optical properties of the natural photonic structures were separated. While water and aqueous sodium citrate solutions change the wing reflectance by the alteration of the wing scale position with respect to the wing plane, Au and Ag/Au alloy nanoparticles form a new, hybrid nanostructure with the chitin nanoarchitecture modifying the structural color of the butterfly wings. The optical properties of the new types of hybrid photonic nanoarchitectures (consisting of butterfly wings and plasmonic nanoparticles) are different from those of the components.